Exploring global interregional food system's sustainability using the functional regions typology. (May 2021) - Fridman, Dor; Koellner, Thomas; Kissinger, Meidad
Highlights: We develop the functional regions typology to assess food systems' sustainability. We quantify the level of sustainability of the supply of four major staples. Over 33% of the global calorie intake is from the least sustainable regions. The typology captures hidden tradeoffs and interregional connections. International trade can increase the sustainability of national food supply. Abstract: Maintaining food security and environmental integrity over time requires a transition towards sustainable food systems. This paper analyzes different dimensions of national food supply sustainability on a global scale. By focusing on four food staples: wheat, rice, maize, and soybeans, the analysis identifies production regions that are more or less environmentally sustainable. It explores the dependence of different countries on calories supplied by these regions. These four staples' production requires 648 million hectares of cropland and about 559 cubic kilometers of irrigation water. It also leads to several environmental impacts, including potential soil loss and species loss. Yet, these impacts and pressures are spread unevenly across agricultural systems. We find that over one-third of the global calorie intake originates from regions with a high per ton environmental impacts. Although most consumed calories are from domestic sources, traded calories mostly originate from environmentally suitable production regions, increasing importing countries' food supply sustainability. This analysis also reveals interregional tradeoffs, where food imports into one region (increased food provision) is associated with high environmental impact in production regions. Further, this typology allows identifying an elusive, often overlooked interregional connection. That is the potential loss of future ecosystem service flow from countries with the lower gross domestic product per capita and high biodiversity. To date, those countries rely primarily on domestic staple production, which puts pressure on vulnerable local ecosystems. Species loss in those regions reduces the potential future interregional flows of genetic material. Alternatively, conservation combined with food imports can maintain diversity and the potential flow of genetic material from those regions. The functional regions typology provides a complete assessment of the interregional connections that make up the global food system. Therefore, it is useful for informing policy analysts and policymakers of a broader collection of stakeholders regarding the local environment. It also provides essential information about the suitability of different policy mechanisms to govern interregional systems. Future research shall expand the functional regions' typology to include additional environmental and human-related (e.g., technological), to cover more crops, and to account for other food categories, such as meat.